A Study On Procurement Selection Criteria Of Building Projects In The Malaysian Construction Industry - Lin,, Shui Man (Universiti Sains Malaysia, 2005)
The above statement shows that an appropriate choice of procurement system for a project plays an important role in the success of a project, which would ultimately benefit all the parties who involves. The process of selecting an appropriate procurement method involves a consideration of various factors including the environment of the project itself. Thus, a number of models of procurement selection have been developed. This includes the works of NEDO (1985) and Birrell (1991), which can be used for this research as a guideline. The model was developed’ in the context of Malaysian Construction Industry for this research. The data collection method utilized structured interview and postal questionnaire method. The study found that the combination models of NEDO and Birrell are not applicable in local context.